2018
DOI: 10.15240/tul/001/2019-1-011
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of international tax planning impact on corporate tax gap in the Czech Republic

Abstract: There are many studies focusing on VAT (value added tax) tax gap but very few relevant studies that deal with the corporate income tax loss. The studies vary particularly in their methodology, databases and interpretation. In the case of the Czech Republic the studies resulted in a range between CZK 57 billion tax gap and CZK 12.5 billion corporate tax revenue gain caused by the tax planning. The main aim of the paper is to calculate the corporate income tax effi ciency rate for the Czech Republic and compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Percentage of actual execution of revenues (indicative determinant) for income tax in Ukraine in 2016-2020 was accordingly 111.9; 100.2; 118.5; 111.9; 110.5 with a simultaneous stable increase in budget revenues for the same period in absolute terms: in 2016 -UAH 54. 3 The results of the analysis of the collection of taxes on income and profits, property and consumption confirm the negative impact on the tax potential performance indicators. It is determined that in monetary term, the budget losses during 2015-2019 continued to grow and, over the years they amounted to UAH 55.35 billion, UAH 30.26 billion, UAH 26.8 UAH, UAH 35.74 billion, UAH 42.73 billion accordingly.…”
mentioning
confidence: 77%
“…Percentage of actual execution of revenues (indicative determinant) for income tax in Ukraine in 2016-2020 was accordingly 111.9; 100.2; 118.5; 111.9; 110.5 with a simultaneous stable increase in budget revenues for the same period in absolute terms: in 2016 -UAH 54. 3 The results of the analysis of the collection of taxes on income and profits, property and consumption confirm the negative impact on the tax potential performance indicators. It is determined that in monetary term, the budget losses during 2015-2019 continued to grow and, over the years they amounted to UAH 55.35 billion, UAH 30.26 billion, UAH 26.8 UAH, UAH 35.74 billion, UAH 42.73 billion accordingly.…”
mentioning
confidence: 77%
“…However, the tax gap in relation to the issues of income taxes and fair taxation (above all in relation to MNEs) have been attracting more and more attention globally in the last few decades (for research on some aspects see Tax Gap Project Group, 2018). This has also been the case in the Czech Republic (see, for example, studies by Finardi and Vančurová, 2014;Moravec, Rohan and Hinke, 2019). The existence of the tax gaps in connection with breaches in the principles of fair taxation have initiated an OECD action plan (OECD, 2013), which naturally includes the issue of transfer pricing.…”
Section: Summary Of Findingsmentioning
confidence: 94%
“…Sanz-Sanz et al (2016) argue that lower imports and consumption will result in lower revenues from customs, and especially value-added tax. Moravec et al (2019) analyzed corporate income tax in the Czech Republic and their results showed that the corporate tax revenue loss is not such a substantial issue compared to the value-added tax gap problem. Accordingly, Chan and Ramly (2018) highlight that value-added tax is a powerful tool to increase tax revenues in developing economies.…”
Section: Literature Reviewmentioning
confidence: 99%